2010
DOI: 10.1002/etc.309
|View full text |Cite
|
Sign up to set email alerts
|

The influence of natural organic matter on the toxicity of multiwalled carbon nanotubes

Abstract: Engineered carbon nanostructures, such as multiwalled carbon nanotubes (MWNTs), are inherently hydrophobic and are not readily stable in aqueous media. However, the aqueous stability and bioavailability of these nanotubes may be influenced by the water quality parameters such as ionic strength, pH, and natural organic matter (NOM). Natural organic matter adsorbs onto the surface of MWNTs, effectively covering the hydrophobic surface and resulting in increased aqueous stability. This enhanced stability is likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
107
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(123 citation statements)
references
References 39 publications
13
107
3
Order By: Relevance
“…The role that these surface coatings have in CNP toxicity is not yet well understood, but limited numbers of studies have investigated this topic using Daphnia [69,75]. Multiwalled carbon nanotubes wrapped with different types of NOM possessed significantly different LC50 values [69].…”
Section: Cnp Dispersion Methods For Ecotoxicity Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…The role that these surface coatings have in CNP toxicity is not yet well understood, but limited numbers of studies have investigated this topic using Daphnia [69,75]. Multiwalled carbon nanotubes wrapped with different types of NOM possessed significantly different LC50 values [69].…”
Section: Cnp Dispersion Methods For Ecotoxicity Testsmentioning
confidence: 99%
“…The role that these surface coatings have in CNP toxicity is not yet well understood, but limited numbers of studies have investigated this topic using Daphnia [69,75]. Multiwalled carbon nanotubes wrapped with different types of NOM possessed significantly different LC50 values [69]. Grafting PEI coatings onto MWNTs to give the CNTs positive, negative, or neutral surface charges increased the toxicity of the MWNTs compared with unmodified nanotubes, but the toxicity did not show a clear trend with regard to the surface charge [75].…”
Section: Cnp Dispersion Methods For Ecotoxicity Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include nanomaterial measurement and characterization, running appropriate controls, and assessing the appropriate endpoints. For example, several investigators have concluded that the toxicity of carbon nanotubes was not due to some biochemical interaction; rather, the toxicity was due to clogging the intestinal tract and interfering with food processing and assimilation [16]. The evolution of ecotoxicity testing methods can be viewed as a refinement in the current toolbox of methods.…”
Section: Assessing Hazardmentioning
confidence: 99%
“…For example, the adsorption of natural organic matter to multiwalled carbon nanotubes increases the aqueous stability of hydrophobic nanotubes and toxicity of the adducts to daphnia. 22 The tributyltin/nano-TiO 2 adduct is more toxic to abalone embryos than tributyltin alone. 23 Similar synergistic toxicities to aquatic organisms have also been found for As, Pb, Cu, and Cd in the presence of nano-Al 2 O 3 , nanoFe 2 O 3 , and nano-TiO 2 .…”
Section: ■ Introductionmentioning
confidence: 99%